PERSPEKTIF PERTOLONGAN PERSALINAN OLEH DUKUN BAYI DI DESA BUMIJAWA KECAMATAN BUMIJAWA KABUPATEN TEGAL TAHUN 2009 - Siswati; Siti Erniyati B.P; Kodijah ,SST (LPPM Universitas Pekalongan, 2011)
In Bumijawa village, Bumijawa, Tegal in 2009, the giving birth to health workers was only 63,1%, it is so far from the target of 90% in 2010. It shows that the role of traditional birth attendans is still high. This study is aimed to find information about giving birth aid by traditional birth attendans from the mother and traditional birth attendans aspect in Bumijawa village, Tegal. The research design used was qualitative approach. The population consists of two groups. The first group off all the mothers who gave birth to traditional birth attendans, and the second group are all traditional birth attendans who live in Bumijawa village, Bumijawa, Tegal. The data gathering technique used for the first group is in depht interview, and for the second group is Focus Group Discussion (FGD).The gathered data was examined with triangulation technique. The result of this study shows that mothers had different perception about giving birth aid that is done by traditional birth attendans. All of traditional birth attendans have same perception about the meaning of giving birth, the parturition term nursing and the system of reporting that is done by traditional birth attendans. It is needed a controlling and coaching program for active traditional birth attendans continually in order to get the scope of giving birth aid target by health worker that is 90% in 2010 can be reached.Key words : Giving birth aid, traditional birth attendans